The role of Neurochemicals, Stress Hormones and Immune System in the Positive Feedback Loops between Diabetes, Obesity and Depression - Wilson, Julian B.; Epstein, Ma’ayan; Lopez, Briana; Brown, Amira K.; Lutfy, Kabirullah; Friedman, Theodore C. (Frontiers in Endocrinology, 2023)
Type 2 diabetes mellitus (T2DM) and depression are significant public health and socioeconomic issues. They commonly co-occur, with T2DM occurring in 11.3% of the US population, while depression has a prevalence of about 9%, with higher rates among youths. Approximately 31% of patients with T2DM suffer from depressive symptoms, with 11.4% having major depressive disorders, which is twice as high as the prevalence of depression in patients without T2DM. Additionally, over 80% of people with T2DM are overweight or obese. This review describes how T2DM and depression can enhance one another, using the same molecular pathways, by synergistically altering the brain’s structure and function and reducing the reward obtained from eating. In this article, we reviewed the evidence that eating, especially high-caloric foods, stimulates the limbic system, initiating Reward Deficiency Syndrome. Analogous to other addictive behaviors, neurochemical changes in those with depression and/or T2DM are thought to cause individuals to increase their food intake to obtain the same reward leading to binge eating, weight gain and obesity. Treating the symptoms of T2DM, such as lowering HbA1c, without addressing the underlying pathways has little chance of eliminating the disease. Targeting the immune system, stress circuit, melatonin, and other alterations may be more effective.